PENGARUH GAYA KEPEMIMPINAN, PRESTASI KERJA, LINGKUNGAN KERJA, SARANA DAN PRASARANA TERHADAP MOTIVASI KERJA PEGAWAI ADMINISTRASI - Rahmat Rahmat; Rahmawati Rahmawati (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
This study aims to determine how the work motivation of education staff in supporting administrative services, leadership style, work performance, work environment, facilities and infrastructure at IAIN Palopo. Design/methodology/approach – In this study, a quantitative approach was used. The data collected were 100 employees at IAIN Palopo Palopo Campus using a structured questionnaire, and the theoretical model was tested using the least partial structured equation modeling (PLS-SEM). In addition, convergent validity and discriminant validity were assessed. Findings - The desired results indicate that all variables were found to have a positive and significant influence on the work motivation of educational staff supporting administrative services, leadership style, work performance, work environment, facilities and infrastructure at IAIN Palopo. Practical implications – This research adds to the literature on work motivation of education personnel, and it is also beneficial for the academic community because it shows the ways and effects of working, employee loyalty, and quality of work. Therefore, this will help the leadership of a university in analyzing the motivations of employees in working in the work environment of an agency.